2003
DOI: 10.1352/0047-6765(2003)041<0007:abacfo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Behavior and Cognitive Function of Adults With Down Syndrome: Modeling Change With Age

Abstract: Fifty-eight adults with Down syndrome (ages 31 to 56 years at time of first testing, mean age, 43.5) were assessed longitudinally over 10 years for the purpose of modeling aging-related change in cognitive function and adaptive behavior. Cognitive function was assessed seven times using the Woodcock-Johnson Tests of Cognitive Ability-Revised Early Development Battery. Adaptive behavior was evaluated five times using the Inventory for Client and Agency Planning. Multi-level (hierarchical linear) modeling proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 29 publications
3
34
1
2
Order By: Relevance
“…Elderly adults with DownÕs syndrome are likely to be as much at risk of developing many of these age-associated conditions as the general elderly population. In addition, with several longitudinal studies confirming a premature aging process in DS adults, these conditions might also be observed at a much earlier age in people with DS [6,[52][53][54].…”
Section: Impact Of Aging On Eating Drinking and Swallowing In The Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Elderly adults with DownÕs syndrome are likely to be as much at risk of developing many of these age-associated conditions as the general elderly population. In addition, with several longitudinal studies confirming a premature aging process in DS adults, these conditions might also be observed at a much earlier age in people with DS [6,[52][53][54].…”
Section: Impact Of Aging On Eating Drinking and Swallowing In The Gmentioning
confidence: 99%
“…Although an increasing number of more recent studies look at the effects of aging on cognitive function in DS [6], there have been no published studies to date that examine how the aging process might affect specifically EDS function in DS individuals. As a consequence, early-stage dysphagia may go undiagnosed.…”
mentioning
confidence: 99%
“…Den avdekker også endring i adaptiv atferd hos personer med annen utviklingshemning. Alzheimers sykdom er vanskelig å diagnostisere da mange symptomer kan vaere sammenfallende med andre lidelser i et tidlig stadium av sykdommen (Burt og Aylward 1999, Hawkins et al 2003, Reeve 2003. Det krever langt mer omfattende undersøkelser enn ABDQ for å diagnostisere Alzheimers sykdom.…”
Section: Diskusjonunclassified
“…Dette øker risikoen for ytterligere svikt i adaptiv atferd når de blir eldre. Det kan vaere problematisk å skille Alzheimers sykdom fra svekkelse som skyldes andre årsaker som redusert hørsel, syn, stoffskiftelidelser, depresjon eller bivirkninger av psykofarmaka, i saer hos personer med utviklingshemning (Burt og Aylward 1999, Hawkins et al 2003. Bruk av psykofarmaka kan påvirke initiativ, konsentrasjon og evnen til å laere.…”
unclassified
“…The maintenance of good health and the application of additional external resources when ill health does occur are likely to be of particular concern for persons with intellectual disabilities, given that when combined with existing disabilities, relatively small additional health concerns can have major implications for independence [8]. Hawkins et al [9] point out that most information on decline and need, at least for persons with Down syndrome, has been based on studies with cross-sectional designs and may therefore exaggerate the rate of decline. Using a longitudinal approach, it was found that decline for persons with Down syndrome did appear to occur on average 10 years earlier than for the general population, and although short-term memory decline was similar to the general population, long-term memory in persons with Down syndrome declined after age 39 at a faster rate [9].…”
Section: Introductionmentioning
confidence: 99%